2006
DOI: 10.1017/s0952523806233467
|View full text |Cite
|
Sign up to set email alerts
|

Visual sensitivity to color errors in images of natural scenes

Abstract: Simple color-difference formulae and pictorial images have traditionally been used to estimate the visual impact of color errors introduced by image-reproduction processes. But the limited gamut of RGB cameras constrains such analyses, particularly of natural scenes. The purpose of this work was to estimate visual sensitivity to color errors introduced deliberately into pictures synthesized from hyperspectral images of natural scenes without gamut constraints and to compare discrimination thresholds expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
1
23
1
Order By: Relevance
“…The worst case fitted 91% and the best 100%. For the original images of the paintings, the average chromatic error for the pixels out of gamut expressed in CIELAB color space was E* ab = 2.4, i.e., near threshold for complex images (Aldaba, Linhares, Pinto, Nascimento, Amano & Foster, 2006, CIE, 2011, Liu, Huang, Cui, Luo & Melgosa, 2013. For rotations of the color gamut, gamut compression occurred as each color out of gamut 8 was projected to the closest one displayable.…”
Section: Stimuli and Experimental Set-upmentioning
confidence: 99%
“…The worst case fitted 91% and the best 100%. For the original images of the paintings, the average chromatic error for the pixels out of gamut expressed in CIELAB color space was E* ab = 2.4, i.e., near threshold for complex images (Aldaba, Linhares, Pinto, Nascimento, Amano & Foster, 2006, CIE, 2011, Liu, Huang, Cui, Luo & Melgosa, 2013. For rotations of the color gamut, gamut compression occurred as each color out of gamut 8 was projected to the closest one displayable.…”
Section: Stimuli and Experimental Set-upmentioning
confidence: 99%
“…But the visual significance of colorimetric errors in complex images is still an open question that has not been completely resolved. Previous experiments 19 have found that the observers' ability to discriminate between images needed on average a CIELab color difference of about 2.2, although large variations around this mean for a variety of images were also found. Because the illuminant-free images were obtained here by just using a three-channel RGB digital camera and not a spectral device, the results could be biased by these psychophysical and physical constraints.…”
Section: Discussionmentioning
confidence: 82%
“…Because the average color difference was around 7 ΔE Lab units our results confirm that so far there is no easy way to assess colorimetric accuracy in the reproduction of color images. 19 Color accuracy can only be assessed on the basis of a pixel-by-pixel calculation, which merely gives approximate overall perceptible differences after averaging out the results for the whole image. …”
Section: Color Albedo Recovery Outdoorsmentioning
confidence: 99%
“…In a previous study, Aldaba et al [9] segmented the image in the CIELAB space into cubes. Each cube then suffer the application of a ∆E * ab error and it was concluded the existence of an error perception for ∆E * ab larger than 5 units.…”
Section: Database Manipulationmentioning
confidence: 99%